Perfluorodecanoic acid promotes adipogenesis via NLRP3 inflammasome-mediated pathway in HepG2 and 3T3-L1 cells. (January 2023) - Wang, Taotao; Xu, Hong; Guo, Yu; Li, Zhanming; Ye, Hua; Wu, Liang; Guo, Yuanxin; Wang, Dongxu
Abstract: Perfluorodecanoic acid (PFDA) is a toxic persistent pollutant that is extensively used in food applications, such as food packaging and cookware. Emerging evidence indicates that PFDA exposure were associated with higher plasma triglyceride concentration in human. In contrast, it is unknown how PFDA might affect adipogenesis. To explore the effects and underlying mechanisms of PFDA on lipid metabolism in this study, both HepG2 cells and 3T3-L1 differentiation model were used. The results showed that PFDA promoted the cellular triglyceride accumulation and triglyceride content in concentration-dependent manners. Furthermore, PFDA activated the NLRP3 inflammasome, which is crucial for the induction of lipogenic genes expression including fatty acid synthase (FAS), hydroxymethylglutaryl coenzyme A synthase (HMGCS), and stearoyl-CoA desaturase 1 (SCD1). Additionally, PFDA-induced adipogenesis was abolished by caspase-1 inhibitor and siNLRP3 in HepG2 cells. Moreover, after PFDA treatment, the expression of SREBP1, an important regulator of lipid metabolism, was increased, as well as its target genes, and PFDA-induced SREBP1 enhanced expression can be abolished by caspase-1 inhibitor and siNLRP3 as well. Together, these results provide to understanding of the potential health implications of exposure to PFDA on lipid accumulation, and suggest that PFDA can promote adipogenesis via an NLRP3 inflammasome-mediated SREBP1 pathway. Graphical abstract: Image 1 Highlights: Perfluorodecanoic acid (PFDA) induced adipogenesis in HepG2 and 3T3-L1 cells. PFDA promoted cellular triglyceride accumulation and enhanced triglyceride levels . NLRP3 knockdown abolished the increased triglyceride accumulation and SREBP1 expression induced by PFDA . PFDA activated NLRP3 inflammasome-mediated SREBP1 expression .